A Comprehensive Comparative Analysis of Mediation Practices in Indonesia and Malaysia - Muhammad Amrullah Drs Nasrul; Nurin Athirah Mohd Alam Shah; Wan Noraini Mohd Salim; Devi Seviyana (Khazanah Hukum, 2024)
Mediation is one of the Alternative Dispute Resolution (ADR) that emphasises a mutually agreeable resolution and incorporates a win-win situation between parties. Mediation is not a rare concept in Indonesia and Malaysia. People in Indonesia and Malaysia have long used mediation in their daily lives as mediation has been proven to be effective since long ago. Due to its extensive use in Indonesia and Malaysia, a comprehensive study was carried out by the researcher to identify the comparison of mediation in Indonesia and Malaysia. In this paper, the researcher will review the practice of mediation in Indonesia and Malaysia via a comparison analysis where the researcher employs a qualitative approach via library-based research. Many reference sources and reading materials have been used by researchers to see similarities and differences between these two countries. The result of this study affirms that mediation practices in Indonesia and Malaysia are quite similar, despite being governed under a different law and regulations. In addition to having many similarities, one of the things that attracted the researcher's attention is that both countries have their challenges in carrying out mediation. Therefore, this aspect of the challenge also needs to be touched upon so that mediation can be conducted in both countries smoothly. It is also hoped that with this study, in the future, this study can also be used as a guide or manual in discussing mediation for both countries.